Republic of Slovenia : Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on the following topics; Banking Supervision, Securities Regulation, Insurance Supervision, and Payment Systems. (IMF Staff Country Reports; Country Report ;, 2001)
This report on the Financial System Stability Assessment presents the main findings and overall assessment of the Republic of Slovenia's financial system. The paper analyzes the reports on the Observance of Standards and Codes on banking supervision, securities regulation, insurance supervision, and payment systems. The assessment confirms the strong supervisory standards attained in Slovenia, and noted the current absence of consolidated supervision and the regulatory gap governing investment guidelines for insurance companies, and the need for a strong financial system.